Międzynarodowa ochrona małżeństwa - Sandorski, Jan (Wydział Prawa i Administracji UAM, 1986)
The article was prepared within the research scheme on the subject II. 10 of the crucial problem 11.9. The subject is concerned with the protection of family in international law. The international protection of marriage is one of its elements. Numerous international acts (the Covenant on Civil and Political Rights) contain provisions from which it results that founding a family follows a conclusion of matrimony. It is emphasised in the article that international law provisions are not limited to the protection of institutionalized family but is also concerned with the natural family. A variety of problems to discuss, which are difficult to settle is related to the issue of marriage protection. One could only mention here religious marriages or a polygamous marriage. Neither in internal nor in international law there exists an exhaustive, explicit and juridically correct definition of family and marriage. The notion of marriage can be therefore reconstructed on the grounds of the provisions related to the rights and obligations of spouses and to conclusion, durability, nullity and cessation of marriage. It follows that marriage is a permanent legal relation linking two persons of a different sex who have concluded a legal transaction known as a conclusion of matrimony, on the basis on family law binding on a given territory, in order to realize social tasks of a family established in that manner. Next, the author presents the development of international norms concerning the protection of marriage, indicating the fact that the protection of married woman's rights was at its origins. The international practice related to marriage stesses strongly the principle of equal rights of a husband and wife. The most elaborated shape was given to that principle in the declaration and convention on abolishing discrimination of women (1967 and 1979). A notice contained in art. 6 of the Declaration might be of some interest in this context, it results from it that the equality should not prejudice the unity of marriage. Another important problem regulated in multilateral agreements is the citizenship of married women. International law favors the conception of the autonomous citizenship of a woman. A husband is thus loosing his leading position in the union. Yet, the marriage should not be grounded on a dominating position of one of the sides. At the end of the article the author discusses the crucial legal questions pertaining conclusion and recognition of matrimony in the light of international law.
International Protection of Marriage